Logical fallacies in EFL students' undergraduate argumentative writing - Malihah, Nasywa Ayu; Farida, Alief Noor (ELT Forum: Journal of English Language Teaching, 2025)
Argumentative essays were an important part of learning English as a foreign language (EFL) because this genre of writing not only developed language skills but also engaged students in critical thinking. Although grammar and structure was usually the main focus, students often overlooked the sense of logic in their arguments, especially the fallacies or reasoning errors. To address this gap, the researcher used qualitative research to identify the types of logical errors made by EFL students in their argumentative essays at a public university in Semarang and the underlying causes of those fallacies that occurred. A systematic content analysis method based on Mayfield's taxonomy was used to identify types of logical fallacies that categorized into four board categories, manipulation through language, emotion, distraction, and inductive fallacy. Students' argumentative writing was analyzed, and semi-structured interviews were conducted to understand the patterns that implied the causes of logical fallacies. The findings demonstrated that most of the EFL students’ arguments in argumentative writing were influenced by the limitations in their thinking abilities, emotional reasoning, insufficient explicit instruction in critical thinking, and superficial peer feedback. Students also showed a tendency to simplify complex issues, which was evident from the consistent usage of hasty generalizations and false dilemmas in their essays. Based on these findings, it is essential to introduce the knowledge of logical reasoning and assess the credibility and reliability of reasons and evidences that are incorporated in English argumentative writing courses, which would significantly enhance students' critical thinking skills in learning about argumentation. As a result, these findings should be taken into account by educators who aim to equip EFL students with the critical thinking skills that are necessary for constructing a well-structured argument.